Are there HIV-specific Differences for Anal Cancer Patients Treated with Standard Chemoradiotherapy in the Era of Combined Antiretroviral Therapy?. Issue 4 (April 2017) - Martin, D.; Balermpas, P.; Fokas, E.; Rödel, C.; Yildirim, M.
Abstract: Aims: Contradicting evidence exists regarding the safety and clinical outcome of standard treatment in HIV-positive patients with anal cancer. We report on our large, single-centre experience in HIV-positive versus HIV-negative patients treated in the era of combined antiretroviral therapy (CART). Materials and methods: Between 1997 and 2015, 142 patients (42 HIV-positive versus 100 HIV-negative) with anal cancer were treated with standard chemoradiotherapy. Patients received a median dose of 50.4 Gy to the planning target volume; 91 (64%) patients received an external boost to the primary tumour and/or enlarged lymph nodes of 5.4–10.8 Gy. Concurrent chemotherapy was scheduled in the first and fifth weeks of radiotherapy using 5-fluorouracil and mitomycin C. The median follow-up was 51 (range 0–325) months. Results: HIV-positive patients were predominantly male ( P  < 0.001), younger ( P  < 0.001) and had more advanced nodal disease ( P  = 0.042). A dose reduction of chemotherapy was necessary in 38% of HIV-positive patients and in 24% of HIV-negative patients ( P  = 0.39). There was no significant difference in total dose or duration of radiotherapy (median 43 versus 44 days, P  = 0.59). Complete response (81% versus 87%, P  = 0.088), 5 year rates of local failure (26.2% versus 14.9%, P  = 0.176), 5 year rates of distant failure (14.3% versus 8.4%, P  = 0.371) and 5 year overall survival (70.7% versus 78.4%, P  = 0.491) were not significantly different. HIV-positive patients had worse 5 year cancer-specific survival (80.5% versus 93.8%, P  = 0.029) in univariate but not in multivariate analysis ( P  = 0.276). Conclusions: In the CART era, tolerance and clinical outcome are similar between HIV-positive and HIV-negative patients with anal cancer after standard chemoradiotherapy. Highlights: A rather large cohort of HIV-positive patients with anal cancer treated homogenously. No significant differences regarding acute toxicities, compliance and oncological outcome. HIV-positive patients tolerate chemoradiotherapy as well as HIV-negative patients.